The development of acrylic board game as a learning media on subject matter of cells - Rizkika Handayani; Desy Fajar Priyayi; Susanti Pudji Hastuti (Universitas Ahmad Dahlan, 2020)
The use of learning media is known to improve students thinking skills. The interview conducted at SMP N 9 Salatiga indicated that the students had some difficulties in learning about cells. The purposes of this study were to develop learning media and to determine the feasibility of the media in teaching and learning. The research employed the modification of the Borg and Gall development model that was consist of :1) research and information collection, 2) planning, 3) develop a preliminary form of product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing and 9) final product revision. The effectiveness of the product was measured by the N-Gain test. The validation results of the media experts, material experts, and pedagogy experts were 91.6% (very feasible), 85.7% (very feasible), and 80% (feasible), respectively. Also, the responses from educational practitioners and students were 86.6% (very good) and 82.41% (good), respectively. The students learning with media showed an improved cognitive score, based on N-Gain test analysis, compared to that which learning with other media. In conclusion, the